The Impact of Halal Label, Price, And Brand on the Purchase Decision of Bakso Wagyu in Kota Wisata Cibubur - Freddy Pandapotan Simbolon (Bina Nusantara University, 2019)
The objective of this research was to examine the impact of halal labels, prices, and brand on the purchase decision to buy Bakso Wagyu in Kota Wisata Cibubur. It used associative research, and data were collected through a field survey from the Bakso Wagyu outlet in Kota Wisata Cibubur. A set of questionnaires was distributed to 96 customers of Bakso Wagyu outlet in Kota Wisata Cibubur. Multiple regression analysis assessed the impact on purchase decisions of three key constructs of the halal label, price, and brand. The analysis method used correlation analysis, multiple regressions, and hypothesis testing. The results show three components, namely halal label, price, and brand, simultaneously have a significant influence on the purchase decision. However, the halal label was a variable. That are has the most dominant impact. This research indicates the results that halal labels are important for imported products that are consumed by Indonesian people who are mostly Muslim.